Tabaquismo y las alteraciones Hemodinámicas en Mecánicos y operarios agremiados a la asociación interprofesional de El Oro primer semestre 2014. - Muñoz Guerrero, Brenda (2014)
The study was conducted to determine S. smoking and hemodynamic alterations, it was descriptive, cross-sectional, prospective Time In 160 unionized mechanics and operators the Interprofessional Association of El Oro, 2014. During semester primer Taking the hypothesis that the hemodynamic alterations are related to the consumption of snuff.